Explore the caregiving needs of mothers for late preterm neonates post discharge - Elham Asghari; Mahnaz Modanloo; Alireza Irajpour; Homeira Khoddam (Journal of Education and Health Promotion)
Background: Delivered between 34 and 36 weeks of gestation, late preterm neonates account for nearly 70% of all preterm births. While these neonates are often treated as if they were full term, they have different challenges and needs that pose significant caregiving challenges for their families. Therefore, this study aims to explore the needs of mothers in short-term care of late preterm neonates at home. Materials and Methods: This qualitative content analysis study was conducted using the Graneheim and Lundman method from December 2022 to June 2023. In-depth semistructured interviews were conducted with a purposive sample of 18 mothers who had experience in caring for late preterm neonates. The number of sessions was one or two, and the duration of each interview varied from 30 to 60 minutes. Data were analyzed in MAXQDA 10.0 software. Results: The analysis of the interviews led to the identification of 70 primary codes, which were further categorized into 13 subcategories, and finally, three categories emerged, including “Need for Further Information”, “Need to Enhance Caregiving Skills”, and “Support Needs of Mothers”. Conclusion: Providing sufficient information and training in neonate care plays a crucial role in meeting the needs of mothers. Additionally, comprehensive support for mothers can help reduce problems and maintain their physical and mental health. Clarifying the needs of mothers can contribute to the development of home care programs, empower mothers in their self-care aspect, and enhance the quality of home-based care.